Growth Empirics Under Model Uncertainty : Is Africa Different? - Tsangarides, Charalambos (IMF Working Papers; Working Paper ;, 2005)
This paper attempts to identify robust patterns of cross-country growth behavior in the world as a whole and Africa. It employs a novel methodology that incorporates a dynamic panel estimator, and Bayesian Model Averaging to explicitly account for model uncertainty. The findings indicate that: (i) in addition to initial conditions, various economic factors such as higher investment, lower inflation, lower government consumption, better fiscal stance, improved political environment, exogenous terms-of-trade shocks, and fixed geographical factors are robustly correlated with growth; (ii) what is good for growth around the world is, in principle, also good for growth in Africa; and (iii) political and institutional variables are particularly important in explaining African growth.